2011
DOI: 10.1021/ic200517r
|View full text |Cite
|
Sign up to set email alerts
|

Encapsulation versus Aggregation of Metal–Organic Cages Controlled by Guest Size Variation

Abstract: The strength and mode of binding (inside vs outside) of bisanionic guest molecules to a cationic, self-assembled metal-organic cage depend on their size and the stoichiometry of the addition. Herein we show that the composition of the solid/liquid phase of a heterogeneous system can be kinetically controlled by the order of the addition of two different guest compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
33
0
3

Year Published

2012
2012
2016
2016

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 63 publications
(36 citation statements)
references
References 18 publications
0
33
0
3
Order By: Relevance
“…The highest binding affinities were found for bis‐sulfonate guests with the best match between the guest's size and the Pd⋅⋅⋅Pd separation. Besides this, the authors also showed that addition of a second equivalent of a bis‐anionic guest resulted in the formation of an insoluble salt due to guest‐mediated ionic interaction between two neighboring cages . Moreover, this host was found to be capable of encapsulating various other guest molecules, notably including metal‐based guests such as the hexamolybdate anion [Mo 6 O 19 ] 2−[36] or even the coencapsulation of two different guest species of the Magnus’ salt type .…”
Section: Interpenetrated Coordination Cagesmentioning
confidence: 99%
“…The highest binding affinities were found for bis‐sulfonate guests with the best match between the guest's size and the Pd⋅⋅⋅Pd separation. Besides this, the authors also showed that addition of a second equivalent of a bis‐anionic guest resulted in the formation of an insoluble salt due to guest‐mediated ionic interaction between two neighboring cages . Moreover, this host was found to be capable of encapsulating various other guest molecules, notably including metal‐based guests such as the hexamolybdate anion [Mo 6 O 19 ] 2−[36] or even the coencapsulation of two different guest species of the Magnus’ salt type .…”
Section: Interpenetrated Coordination Cagesmentioning
confidence: 99%
“…[11] Fujita and co-workers were the first to apply this principle to the selfassembly of discrete stacks of square-planar coordinated M II complexes (M = Pd, Pt, Cu, or Ni) showing metal-metal d-d contacts [12] and spin-spin interaction phenomena [13] inside an organic-pillared coordination box.Recently, we introduced a new supramolecular coordination cage 1 consisting of four rigid, concave ligands and two square-planar coordinated d 8 metal ions, such as Pd II (1 a) or Pt II (1 b), sitting on oppositely arranged poles of a globular structure. [14] The ability of this cage to bind bis(anionic) guest compounds in its interior was studied systematically [15] and led to pH-switchable (pseudo)rotaxanes [16] and a system capable of light-triggered crystallization. [17] We herein report the first example of the rational preparation of a short stretch of pentanuclear stacked platinum compounds of the Magnus salt type, in the form of a discrete host-guest compound based on cage 1 in solution and in the solid state Figure 1).The derivatives of Magnus salt having the formula {[PtY 4 ][PtX 4 ]} n (X = Cl À or Br À ; Y= neutral N-donor ligands, NH 3 , NH 2 R, or pyridine) are characterized by an alternate, face-to-face stack of the dicationic and dianionic complexes.…”
mentioning
confidence: 99%
“…Recently, we introduced a new supramolecular coordination cage 1 consisting of four rigid, concave ligands and two square-planar coordinated d 8 metal ions, such as Pd II (1 a) or Pt II (1 b), sitting on oppositely arranged poles of a globular structure. [14] The ability of this cage to bind bis(anionic) guest compounds in its interior was studied systematically [15] and led to pH-switchable (pseudo)rotaxanes [16] and a system capable of light-triggered crystallization. [17] We herein report the first example of the rational preparation of a short stretch of pentanuclear stacked platinum compounds of the Magnus salt type, in the form of a discrete host-guest compound based on cage 1 in solution and in the solid state Figure 1).…”
mentioning
confidence: 99%
“…Fujita and co-workers reported, for example, metal-metal d-d interaction through the discrete stacking of square planar complexes within a M 4 L 6 coordination cage [30]. Clever and coworker described the ability of a M 2 L 4 cage to bind bis(anionic)guest compounds or to form a discrete stack of platinum complexes of the Magnus’ salt type [3132]. Moreover Crowley and coworkers recently published the preparation of a dipalladium(II) cage complex using 2,6-bis(pyridin-3-ylethynyl)pyridine ligand, capable of binding two molecules of cis -platin within its cavity [33].…”
Section: Introductionmentioning
confidence: 99%